Strategi dan Marketing Politik Caleg Anwar Al Sadat Dalam Pileg 2019 Dapil Palembang II Sumsel - Sepriansyah, Muhamad; Yazwardi, Yazwardi; Zalpa, Yulion (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2021)
The election of legislative candidates is a legitimate link between the people and the government in a democratic society. Political strategy is a political force that will occupy a power in the future, the strategy used is to use battle to win wars and aims to achieve peace. The purpose of this study was to determine the strategy carried out by M. Anwar Al Syadat in the 2019 legislative elections in the Palembang II electoral district. This research is field research or